Jumping injuries: Their cause, possible prevention and rehabilitation - Burnett, A. (1999)
There are many types of jumping injuries which may cause the athlete pain, and these could include (but is by no means an exhaustive): Stress fracture of feet or shins - the most common sites are the navicular bone in the foot and the tibia (Figure 1) Achilles tendinitis - the achilles tendon (heel cord) begins to inflame and degenerate (Figure 2) Plantar fasciitis - inflammatory condition of the plantar fascia accompanied by a sharp pain in the underside of the foot (Figure 3) Anterior compartment syndrome - pressure increase within the confined space of the front tibial (shin) muscles (Figure 1) Medial shin splints - inflammation of the deep fascial medial tibial attachment (Figure 1) Chondromalacia patella - articular cartilage softening underneath the patella (Figure 1). Patella tendinitis - degeneration and inflammation of the patella tendon (Figure 1) Spondylolysis - unilateral or bilateral fracture of the pars interarticularis of the vertebrae (Figures 4 and 5) Spondylolisthesis - vertebral body is displaced anteriorly on the vertebral body below often caused by a bilateral spondylolysis (Figures 4 and 5) Annular bulge - Outside portion of the intervertebral disc extending beyond the margin of the vertebrae possibly imposing on the sciatic nerve (Figures 4 and 5). The cause of these injuries in field event athletes and their possible prevention and rehabilitation is the focus of this article. This article is not meant to replace the role of a sports physician or physiotherapist, rather to educate the coach.